Micromorphological and phytochemical survey of Ballota acetabulosa (L.) Benth. (14th May 2021) - Giuliani, C.; Bottoni, M.; Ascrizzi, R.; Milani, F.; Falsini, S.; Papini, A.; Flamini, G.; Fico, G.
Abstract: Within the Open Science project entitled 'Botanic Garden, factory of molecules', a multidisciplinary study approach was applied to Ballota acetabulosa (L.) Benth., at the Ghirardi Botanic Garden (Toscolano Maderno, BS, Italy). Micromorphological and histochemical investigations were performed on the secreting structures of the vegetative and reproductive organs under light, fuorescence and electronic microscopy. Concurrently the characterization of the volatiles spontaneously emitted from leaves and flowers were examined. Four trichome morphotypes were identified: peltate and short‐stalked, medium‐stalked and long‐stalked capitate trichomes, each with a specific distribution pattern. The histochemical analysis was confirmed using ultrastructural observations, with the peltates and long‐stalked capitates as the main sites responsible for terpene production. The head‐space characterization revealed that sesquiterpene hydrocarbons dominated both in leaves and flowers, with γ‐muurolene, β‐caryophyllene and ( E )‐nerolidol as the most abundant compounds. Moreover, a comparison with literature data concerning the ecological roles of the main compounds suggested their dominant roles in defence, both at the leaf and flower level. Hence, we correlated the trichome morphotypes with the production of secondary metabolites in an attempt to link these data to their potential ecological roles. Finally, we made the obtained scientific knowledge available to visitors of the Botanic Garden through the realization of new labelling dedicated to B. acetabulosa that highlights the 'invisible', microscopic features of the plant. Abstract : In Ballota acetabuolosa, peltates and long‐stalked capitates are responsible for terpene production. γ‐Muurolene, β‐caryophyllene and ( E )‐nerolidol prevail in the foliar and floral VOC profiles.